2009
DOI: 10.1093/jjco/hyp029
|View full text |Cite
|
Sign up to set email alerts
|

Vessel-contouring-based Pelvic Radiotherapy in Patients with Uterine Cervical Cancer

Abstract: Contoured vessels can be used as surrogate markers for location of the pelvic lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Margins are designed around blood vessels which serve as good surrogate targets for regional nodes (7,8,12,20). Chao and Lin (12) studied the pelvic node distribution in patients with uterine cervical cancer who underwent lymphangiography.…”
Section: Discussionmentioning
confidence: 99%
“…Margins are designed around blood vessels which serve as good surrogate targets for regional nodes (7,8,12,20). Chao and Lin (12) studied the pelvic node distribution in patients with uterine cervical cancer who underwent lymphangiography.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al, [11] demonstrated using intravenous ultra small particles of iron oxide (USPIO) MRI that 7mm margin around vessels achieved 88% nodal coverage. Uno et al, [32] showed 7-10 mm margin proved to be an adequate coverage in 50 cervix cancer patients in whom none developed marginal recurrence. Similar; practice of giving 7mm margin is followed by guidelines by Small et al, [13] Toita et al, [14] and Lim et al [16] Taylor's guidelines [11] recommend to start contouring common iliac vessels from aortic bifurcation.…”
Section: Ctv Nodal (Ctv 1)mentioning
confidence: 96%